2014
DOI: 10.1089/ped.2014.0332
|View full text |Cite
|
Sign up to set email alerts
|

Oral Immunotherapy for Treatment of Immunoglobulin E-Mediated Food Allergy: The Transition to Clinical Practice

Abstract: Today, there is neither an effective nor an active treatment for food allergy. Allergy immunotherapy has been proposed as an attractive strategy to actively treat food allergy. Oral immunotherapy (OIT), also known as oral desensitization, is a method of inducing the body's immune system to tolerate a food that causes an allergic overreaction. It has been studied for the use in treatment of immunoglobulin E-mediated food allergy to the most common foods, including milk, egg, and peanut. OIT has been able to des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 57 publications
(91 reference statements)
1
13
0
6
Order By: Relevance
“…There is evidence that this new approach is changing the management paradigm in food allergy, and in our opinion, like other authors [180], possibly it´s time for the practice of SOTI in medical centers with medical staff trained and under secure supervision of his risks.…”
Section: Resultssupporting
confidence: 58%
“…There is evidence that this new approach is changing the management paradigm in food allergy, and in our opinion, like other authors [180], possibly it´s time for the practice of SOTI in medical centers with medical staff trained and under secure supervision of his risks.…”
Section: Resultssupporting
confidence: 58%
“…However, many studies have reported achieving encouraging results using oral immunotherapy (OIT) to treat CMA or hens' egg allergies (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Meta-analyses have shown that studies to date have included small numbers of patients (13)(14)(15) and some of them have also included toddlers, which is a stage when milk allergies often resolve themselves naturally (6,11). Dosing protocols have varied from small allergen amounts that aim to protect against accidental exposures to large allergen amounts that aim to induce tolerance (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…However, allergen avoidance, particularly in case of food allergies and commercially prepared food, is difficult to be completely accomplished: 40-100% of deaths due to food anaphylaxis arise from the consumption of meals, which were prepared away from home [60]. Therefore, a strict control of the allergen content in alimentary products and proper labeling should be constantly provided together with respective legal regulation [64].…”
Section: Allergen Detectionmentioning
confidence: 99%